Children Tooth Brushing Behavior and Oral Microbiota: A Pilot Study - Susana J. Calderon; Seon Yoon Chung; Christopher J. Fields; Nathan T. Mortimer (MDPI AG, 2021)
By age 17, almost 80% of US children have dental caries resulting from cariogenic bacteria that could be reduced with tooth brushing. This cross-sectional, correlational pilot study aims to understand the association between tooth brushing and oral microbiota in children. Oral specimens and survey data were collected from a convenience sample of 16 children, aged 7-12, and attending a community dental clinic. Descriptive statistics were used to analyze sample characteristics and tooth brushing behavior. Biospecimens were analyzed using Polymerase Chain Reaction (PCR) amplification and 16S ribosomal RNA (rRNA) gene sequencing. Beta diversity measures were compared across tooth brushing groups using Permutational Analysis of Variance (PERMANOVA) and Analysis of Similarities (ANOSIM) tests in R. The frequency of tooth brushing in this sample was once a day (brush1; 43.8%), twice a day (brush2; 43.8%), or more than twice a day (12.6%). Major phyla found in the subjects' upper and lower teeth were the following: Proteobacteria, Fusobacteria, Firmicutes, Bacteroidetes, and Actinobacteria. The relative abundance of Actinobacteria was significantly lower in brush2 as compared to brush1 (p = 0.001), whereas the relative abundance of Proteobacteria was significantly higher (p = 0.025). The association between tooth brushing frequency and microbiome beta diversity was significant (p = 0.005 by PERMANOVA and p = 0.002 by ANOSIM). This study demonstrates that tooth brushing frequency could affect the proportional composition of the oral microflora. Additional research on the implication of these changes is warranted.